2020
DOI: 10.3390/ani10030440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yeast (Saccharomyces Cerevisiae) Probiotics Supplementation on Bone Quality Characteristics in Young Japanese Quail (Coturnix Japonica): The Role of Sex on the Action of the Gut-Bone Axis

Abstract: The aim of the study was to investigate the changes in bone geometry, histological structure, and selected mechanical characteristics in young male and female Japanese quails supplemented with Saccharomyces cerevisiae. Quails were fed a basal diet containing no yeast or a basal diet supplemented with 1.5% (15 g per 1 kg of diet) of inactive S. cerevisiae, for a period of 42 days. S. cerevisiae inclusion had no effect on bone weight, length, and density, diaphysis geometry (cross-sectional area, wall thickness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The relationship between the decrease in colonic myenteron thickness and colonic function was not investigated in the current study. It may be surmised that there could have been difficulties observed with regards to colonic movement, but (1) it was not investigated and ( 2) it has been shown that maternal HMB treatment has a beneficial effect on general and skeletal development of newborns and weaned piglets through its anabolic action and ( 3) it has been proven that the gut-bone axis exists, thus bone development is dependent on gut function (Tomaszewska et al, 2018Muszyński et al, 2020). Moreover, diarrhea or other intestinal disorders were not observed in the piglets from birth until weaning.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the decrease in colonic myenteron thickness and colonic function was not investigated in the current study. It may be surmised that there could have been difficulties observed with regards to colonic movement, but (1) it was not investigated and ( 2) it has been shown that maternal HMB treatment has a beneficial effect on general and skeletal development of newborns and weaned piglets through its anabolic action and ( 3) it has been proven that the gut-bone axis exists, thus bone development is dependent on gut function (Tomaszewska et al, 2018Muszyński et al, 2020). Moreover, diarrhea or other intestinal disorders were not observed in the piglets from birth until weaning.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that changes in GIT function are linked with changes in bone homeostasis and bone properties [14,45]. Changes in the structure of the intestinal mucosa results in changes in digestive and absorptive processes within the intestine, which in turn influence general metabolism, including that of bone tissue.…”
Section: Discussionmentioning
confidence: 99%